2021
DOI: 10.1590/1980-57642021dn15-020010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of social cognition after an ischemic stroke: preliminary findings

Abstract: ABSTRACT. The co-occurrence of post-stroke behavioral disorders and cognitive impairment has been extensively investigated. However, studies usually do not include social cognition among the assessed cognitive domains. Objective: To investigate the potential association between facial emotion recognition, a measure of social cognition, and behavioral and cognitive symptoms in the subacute phase of ischemic stroke. Methods: Patients admitted to a Stroke Unit with ischemic stroke were followed up to 60 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
1
0
2
Order By: Relevance
“…The orange light (589 nm, close to 605 nm of our study) was consequently demonstrated to activate greater brain activity in several regions of the frontal lobes, which are alertness and cognition, providing strong evidence in favor of a cognitive role for melanopsin ( 33 ). The occurrence of stroke-related cognitive impairment has been extensively investigated ( 45 ). Neuroanatomical lesions caused by IS on strategic areas such as the hippocampus and white matter might contribute to the pathogenesis of stroke-related cognitive impairment ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The orange light (589 nm, close to 605 nm of our study) was consequently demonstrated to activate greater brain activity in several regions of the frontal lobes, which are alertness and cognition, providing strong evidence in favor of a cognitive role for melanopsin ( 33 ). The occurrence of stroke-related cognitive impairment has been extensively investigated ( 45 ). Neuroanatomical lesions caused by IS on strategic areas such as the hippocampus and white matter might contribute to the pathogenesis of stroke-related cognitive impairment ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Vago et al, 2022). Souza et al (2021) relataram que após um AVC isquêmico, os indivíduos acometidos podem apresentar alterações cognitivas sociais, especificamente de reconhecimento da emoção facial associadas a sintomas comportamentais.…”
Section: Avaliarunclassified
“…Em conformidade a isso, estudos sugerem que associada aos aspectos socioeconômicos, a perda de dentes pode ser um fator de risco para o AVC, devido a alterações nas vias aéreas e predisposição à apneia obstrutiva do sono. A ocorrência de distúrbios comportamentais, comprometimento cognitivo, demência e afasia são comuns após um AVC, sendo que as sequelas motoras são as mais comuns após um AVC, e a identificação dessas condições é essencial para um planejamento adequado da reabilitação (Andreoli et al, 2021;Souza et al, 2021;Vago et al, 2022;Oliveira et al, 2023).…”
Section: Introductionunclassified